A global view came easy for this well‐traveled leader. Issue 4 (14th June 2020) - Enos, Gary
Abstract : Costas Solomou credits his upbringing and educational background for nurturing a lifelong appreciation of the global perspective. A first‐generation college student whose parents emigrated from Cyprus when he was a child, Solomou has long seen the value of a university campus as a global melting pot. He has served since 2019 as Vice President of Enrollment Management at the State University of New York at Geneseo, relocating from his most recent position as Dean of Admissions at George Washington University.